2D Transition‐Metal Silicides as Analogs of MXenes: A First‐Principles Exploration. Issue 6 (4th March 2021) - Lan, Xiaoli; Yu, Linke; Lv, Xiaodong; Li, Fengyu
Abstract : The family of 2D transition metal carbides, carbonitrides, and nitrides (MXenes) has aroused scientific research due to their unique electrical, optical, and chemical properties and their versatile applications. Based on first‐principles calculations, ten transition metal silicide (M2 Si, M = Sc, Ti, V, Cr, Mn, Co, Zn, Y, Nb, and Mo) monolayers are studied. Three stable 2D M2 Si (M = Mn, Co, and Y) crystals are identified through the investigation of thermodynamic, dynamical, and thermal perspectives. Among them, Y2 Si monolayer is a nonmagnetic metal, whereas Mn2 Si and Co2 Si monolayers are antiferromagnetic metals. The three monolayers are chemically inert to H2 and N2, but highly active to O2, and only Y2 Si with its surface functionalized by oxygen exhibits good thermal stability, whose magnetic and electronic properties retain its pristine counterpart. In addition, it is found that the Y2 Si shows good electrocatalytic performance in hydrogen evolution reaction (HER). These stable 2D M2 Si monolayers have potential in the fields of electronics and electrocatalysis. Abstract : As the analogs of MXenes, three 2D transition metal silicides (M2 Si, M = Mn, Co, and Y) show solid stability in terms of thermodynamic, dynamic, and thermal perspectives by first‐principles calculations, but are highly prone to be oxidized by O2 . All the three monolayers are metals, and Y2 Si can serve as a good electrocatalyst for the hydrogen evolution reaction.